Enhanced photocatalytic activity induced by surface plasmon resonance on Ag‐loaded strontium titanate nanoparticles. (1st September 2013) - Yan, Xu; Sun, Shaofang; Hu, Bo; Wang, Xiyou; Lu, Wei; Shi, Weidong
Abstract : Ag nanoparticles‐modified cubic‐like SrTiO3 (STO) are fabricated through a classical hydrothermal and photodeposition method. The prepared Ag‐STO heterogeneous exhibit an efficient photocatalytic activity (∼42% within 1 h reaction time) for degradation of tetracycline under visible‐light irradiation, and Ag deposition with 8 mM AgNO3 exhibited excellent photocatalytic activity. It is considered that this excellent performance results from the surface plasmon resonance of Ag nanoparticles. Meanwhile, the basic principle of the photocatalytic process on the Ag‐STO photocatalyst system is also discussed.